Directed evolution of conformation‐specific antibodies for sensitive detection of polypeptide aggregates in therapeutic drug formulations. Issue 2 (22nd November 2020) - Lou, Wenjia; Stimple, Samuel D.; Desai, Alec A.; Makowski, Emily K.; Kalyoncu, Sibel; Mogensen, Jesper E.; Spang, Lotte T.; Asgreen, Désirée J.; Staby, Arne; Duus, Karen; Amstrup, Jan; Zhang, Yulei; et al.
Abstract: Biologics such as peptides and proteins possess a number of attractive attributes that make them particularly valuable as therapeutics, including their high activity, high specificity, and low toxicity. However, one of the key challenges associated with this class of drugs is their propensity to aggregate. Given the safety and immunogenicity concerns related to polypeptide aggregates, it is particularly important to sensitively detect aggregates in therapeutic drug formulations as part of the quality control process. Here, we report the development of conformation‐specific antibodies that recognize polypeptide aggregates composed of a GLP‐1 receptor agonist (liraglutide) and their integration into a sensitive immunoassay for detecting liraglutide amyloid fibrils. We sorted single‐chain antibody libraries against liraglutide fibrils using yeast surface display and magnetic‐activated cell sorting, and identified several antibodies with high conformational specificity. Interestingly, these antibodies cross‐react with amyloid fibrils formed by several other polypeptides, revealing that they recognize molecular features common to different types of fibrils. Moreover, we find that our immunoassay using these antibodies is >50‐fold more sensitive than the conventional method for detecting liraglutide aggregation (Thioflavin T fluorescence). We expect that our systematic approach for generating a sensitive, aggregate‐specific immunoassay can be readily extended to other biologics to improve the quality and safety of formulated drug products. Abstract : A novel directed evolution strategy was developed to generate conformation‐specific antibodies that recognize polypeptide aggregates composed of a GLP‐1 receptor agonist (liraglutide). The antibodies were integrated into a sensitive immunoassay for detecting liraglutide aggregates and the resulting assay was >50‐fold more sensitive than the conventional method for detecting liraglutide aggregates (Thioflavin T fluorescence). This approach holds significant potential for sensitively detecting peptide aggregates in therapeutic drug formulations as part of the quality control process.